PENDAMPINGAN IBU RUMAH TANGGA (IRT) DALAM INOVASI PRODUK LIMBAH LIDI KELAPA SAWIT SEBAGAI PENGHASILAN TAMBAHAN PADA MASA PANDEMI COVID-19 - Mahfuzi Irwan; Rosdiana Rosdiana; Fauzi Kurniawan (Universitas Negeri Medan, 2020)
This study aims to reveal how product innovation assistance from palm oil waste during the Covid-19 period was carried out in Sei Piring Village, Asahan Regency. The oil palm industry is a macro industry for the source of income for the sei plate villagers. Oil palm is the only resource managed by local communities. As a result of the large number of palm oil industries, the waste of oil palm sticks has become the center of attention by the local community. Especially the housewives in Sei Piring village who wanted to turn the palm oil stick waste into goods that had high selling value as a source of additional income. The lack of skills in the utilization of palm oil stick waste has made local housewives only use palm oil waste to become household broom sticks. The lack of skills in this stick waste innovation has made the villagers of Sei Piring village, especially housewives, unable to develop other crafts. So that the sticky waste is not used very much and has less selling power in the market. Especially during the Covid-19 pandemic, the invasion / decline in the economy was felt by the people of Sei Piring village.